2005
DOI: 10.1210/en.2005-0370
|View full text |Cite
|
Sign up to set email alerts
|

The Aldosterone Synthase (CYP11B2) and 11β-Hydroxylase (CYP11B1) Genes Are Not Expressed in the Rat Heart

Abstract: Aldosterone synthase (CYP11B2) and 11beta-hydroxylase (CYP11B1) catalyze the production of aldosterone and corticosterone, respectively, in the rat adrenal cortex. Recently, there has been some debate as to whether these corticosteroids are also produced in the hearts of rodents and humans, possibly contributing to the development of hypertrophy and myocardial fibrosis. To investigate this, we have used our established, highly sensitive real-time quantitative RT-PCR method to measure CYP11B1 and CYP11B2 mRNA l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 33 publications
2
33
1
3
Order By: Relevance
“…Similar findings were obtained recently by Chai et al 24 We found no significant differences between the cardiac aldosterone content of sham and NPX rats and very low levels of CYP11B2 expression in the heart. Also, Ye et al 16 did not observe any increase in cardiac CYP11B2 in several rat models of cardiac pathology. Therefore, heart aldosterone synthesis appears not to be implicated in cardiac MR activation of experimental chronic renal failure.…”
Section: Discussionmentioning
confidence: 90%
“…Similar findings were obtained recently by Chai et al 24 We found no significant differences between the cardiac aldosterone content of sham and NPX rats and very low levels of CYP11B2 expression in the heart. Also, Ye et al 16 did not observe any increase in cardiac CYP11B2 in several rat models of cardiac pathology. Therefore, heart aldosterone synthesis appears not to be implicated in cardiac MR activation of experimental chronic renal failure.…”
Section: Discussionmentioning
confidence: 90%
“…Although cardiac synthesis of aldosterone has had a relatively long and disputed 40 history, the most recent reports from vigorously controlled studies on levels of steroidogenic enzyme mRNA are widely regarded as providing a definitive negative answer to the question of cardiac aldosterone synthesis. 41,42 This is strong evidence that the protective inverse agonist effect of spironolactone is via MRs, for which spironolactone has much higher affinity than for androgen, progesterone, or GRs. In addition to the report already cited, 20 there are cell culture studies 43,44 in which spironolactone alone produced substantial changes, for example, in integrin expression in neonatal cardiomyocytes.…”
Section: Discussionmentioning
confidence: 98%
“…30 Indeed, in the rat heart, for example, there is little evidence that aldosterone synthase (CYP11B2) and 11(␤)-hydroxylase (CYP11B1) genes are expressed, because there is either extremely low expression of mRNA or protein for steroidogenic enzymes or they are not found at all. 31 Cardiac and vascular MRs have also been demonstrated. 5 Aldosterone induces fibrosis in heart, blood vessels, and kidney, particularly in the presence of high salt.…”
Section: Smooth Muscle Cellsmentioning
confidence: 99%